PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN OPINI AUDIT BADAN PEMERIKSA KEUANGAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Alliyah, Siti -; Karno, Dini Kartika Sari (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2021)
This study aims to analyze the effect of local government characteristics and the audit opinion of the Supreme Audit Agency (BPK) on the financial performance of district/city governments in Central Java Province. This study uses balance panel data, local government budget realization reports, balancing funds, and capital expenditures, an overview of reports on the results of BPK examinations and the number of DPRD members from 35 regencies/cities in Central Java Province from 2014 to 2016 with a total of 105 observations. The data analysis technique uses multiple linear regression. The results showed that the size of local government and prosperity had a significant positive influence on the financial performance of local governments, while capital expenditures, legislative measures, and BPK audit opinions had a significant negative influence on local government financial performance. The coefficient of determination test shows that 80.8% of variations or changes in local government financial performance can be explained by variations in local government size, prosperity, capital expenditure, legislative size, and BPK audit opinion, while the remaining 19.2% is explained by causes other outside the research model Keywords: Local Government Size, Prosperity, Capital Expenditure, Legislative Size, BPK Audit Opinion, Local Government Financial Performance